High performance work systems, technological innovations and firm performance in SME: evidences from Italy. (1st January 2011) - Della Torre, Edoardo; Solari, Luca
The empirical evidence of the past 15 years has shown the existence of a positive relationship between the adoption of organisational innovations and a firm's economic results. However, only few studies focus on the actual adoption and the effectiveness of high performance work systems in small and medium-sized enterprises, and especially so in the case of Italy. Through analysis of an original sample of SMEs in the Milan area, this paper shows that organisational innovations have been introduced in a large part of firms, but in many cases the process of organisational change is not yet complete. Moreover, confirming a large part of the existing evidences, analysis of the relationships with business performance shows that SMEs which have achieved the largest productivity increases are those which have combined investments in the new organisation of work with advanced technologies and with the embeddedness in stable relational networks with other firms.